2018
DOI: 10.1371/journal.pone.0194789
|View full text |Cite
|
Sign up to set email alerts
|

Levels of anti-CMV antibodies are modulated by the frequency and intensity of virus reactivations in kidney transplant patients

Abstract: Anti-CMV (cytomegalovirus) antibody titers are related to immune alterations and increased risk of mortality. To test whether they represent a marker of infection history, we analyzed the effect of viral reactivations on the production of specific antibodies in kidney transplant patients. We quantified CMV-DNAemia and antibody titers in 58 kidney transplant patients before transplantation and during a follow-up of 315 days (standard deviation, SD: 134.5 days). In order to calculate the intensity of the infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Despite prophylaxis, 63% of first episodes reactivation was observed in this group. This finding was in accordance with data of recent literature, 43 to 61.9% CMV seropositive transplant patients had experienced virus reactivation or re-infection by detection of viral DNA [18, 29]. One study [30] demonstrated that transplanted organ of seropositive donor was associated with 49% infection rates in the recipients with lack of prophylactic treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite prophylaxis, 63% of first episodes reactivation was observed in this group. This finding was in accordance with data of recent literature, 43 to 61.9% CMV seropositive transplant patients had experienced virus reactivation or re-infection by detection of viral DNA [18, 29]. One study [30] demonstrated that transplanted organ of seropositive donor was associated with 49% infection rates in the recipients with lack of prophylactic treatment.…”
Section: Discussionsupporting
confidence: 91%
“…However, the active CMV replication is still occurred in the D+/R+ population over the first three months of prophylaxis [17,18], and associated with CMV viraemia or with late-onset disease [19][20][21]. Furthermore, CMV recurrence infections can be developed after the first episode of reactivation in this group [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the immunotoxicity of lead is not strong enough to tip the balance towards recurrence, but could slightly impair the immune system’s capacity to contain the virus quickly when recurrences occur in young adulthood. 32 …”
Section: Discussionmentioning
confidence: 99%
“… 60 Since low socioeconomic status is related to greater cadmium and lead exposures as well as to greater CMV exposure (for instance, from daycare attendance, number of sexual partners, and crowded housing conditions), 48 , 56 we would expect any residual confounding to result in overestimated associations of blood metal concentrations with CMV seropositivity and antibody levels. Finally, while elevations in CMV-specific IgG levels might correlate with the length or frequency of CMV recurrences in immunosuppressed patients, 32 their significance in immunocompetent individuals is unclear. 61 …”
Section: Discussionmentioning
confidence: 99%